The effects of compiler optimizations on embedded system power consumption - Shuhaizar, Daud; R. Badlishah, Ahmad; Nukala S., Murhty (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org